Prefiks Penanda Derajat Chou- dan Oo- dalam Anime Boku No Hiiro Akademia: Futari No Eiyuu: The Degree-Marking Prefixes Chou- and Oo- in the Anime My Hero Academia: Two Heroes - Ketut Ray Wedana Karyasa; Mohamad Arfan Wahid Habibi (Undiksha Press, 2026)
This study examined degree prefixes in Japanese, focusing on the prefixes chou- and oo-, which intensify the meaning of base words without altering their grammatical category. The research addressed the forms, meanings, functions, and applications of these prefixes in Japanese utterances. The study aimed to explain the morphological process of prefixation and the differences in intensity produced by each prefix. Data were collected using the listening-and-note-taking method by observing the linguistic expressions in the anime “Boku no Hiiro Akademia: Futari no Eiyuu”. The analysis was conducted through a descriptive qualitative approach. The results show that chou- functions as a hyper-intensifier with evaluative nuances, while oo- conveys more concrete and quantitative intensity. These prefixes play an essential role in shaping meaning and stylistic expression in the anime’s dialogue.